2019
DOI: 10.3390/sym11111384
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Emission of an Atom Near an Oscillating Mirror

Abstract: We investigate the spontaneous emission of one atom placed near an oscillating reflecting plate. We consider the atom modeled as a two-level system, interacting with the quantum electromagnetic field in the vacuum state, in the presence of the oscillating mirror. We suppose that the plate oscillates adiabatically, so that the time-dependence of the interaction Hamiltonian is entirely enclosed in the time-dependent mode functions, satisfying the boundary conditions at the plate surface, at any given time. Using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…A possibility of exciting the Rydberg atoms passing near the boundary with oscillating parameters ("oscillating effective mirror") was studied in [419]. The influence of the oscillating boundary on the spontaneous emission rate of an atom placed nearby this boundary was considered in [420,421]. The influence of the DCE on the fidelity of the quantum state transfer between two qubits in the ultrastrong coupling regime was studied in [405].…”
Section: Dce and Atomic Excitationsmentioning
confidence: 99%
“…A possibility of exciting the Rydberg atoms passing near the boundary with oscillating parameters ("oscillating effective mirror") was studied in [419]. The influence of the oscillating boundary on the spontaneous emission rate of an atom placed nearby this boundary was considered in [420,421]. The influence of the DCE on the fidelity of the quantum state transfer between two qubits in the ultrastrong coupling regime was studied in [405].…”
Section: Dce and Atomic Excitationsmentioning
confidence: 99%
“…It is worth to remark that in both situations (parallel o perpendicular motions), if the atom's center of mass oscillates harmonically with a frequency Ω cm < Ω, the spectrum of the emitted photons will have three different frequencies ω = Ω, Ω ± Ω cm . A similar phenomenon occurs for an atom in front of an oscillating mirror [6,7], in the adiabatic approximation. Only two frequencies would be present in the spectrum when Ω cm > Ω.…”
Section: A Dirichlet Planementioning
confidence: 52%
“…Introducing the explicit form of the Dirichlet propagator above into (7), and using an entirely analogous approach to the one of [10] we obtain, after some algebra:…”
Section: The Effective Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations have shown that the presence of a dynamical environment can give additional possibilities (not present in the case of a static environment) to manipulate and control radiative properties of atoms or molecules coupled to a quantum field. For example the spontaneous emission of an excited atom located near a perfectly reflecting plate that oscillates adiabatically has been recently discussed [29,30], and it has been shown that the motion of the mirror significantly affects the atomic decay rate, as well as the spectrum of the emitted radiation, exhibiting the presence of two lateral and almost symmetrical peaks, not present in the case of a static boundary [29]. Similar results were also obtained in the case of an excited atom embedded in a dynamical photonic crystal, when its transition frequency is close to the photonic band edge of the photonic crystal [31].…”
Section: Introductionmentioning
confidence: 99%